2009
DOI: 10.1111/j.1440-1797.2008.01046.x
|View full text |Cite
|
Sign up to set email alerts
|

Independent risk factors for renal damage in a series of primary vesicoureteral reflux: A multivariate analysis

Abstract: Our findings suggest that the development of a contracted renal unit is probably due to congenital malformation, more commonly observed in male infants with high-grade reflux.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…Ongoing renal scarring is less common with proper disease recognition and treatment. However, studies report a more significant risk of renal scarring in higher grades of reflux [25,26]. With scarring comes the risk for hypertension, proteinuria, and reflux nephropathy with loss of renal function [27].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ongoing renal scarring is less common with proper disease recognition and treatment. However, studies report a more significant risk of renal scarring in higher grades of reflux [25,26]. With scarring comes the risk for hypertension, proteinuria, and reflux nephropathy with loss of renal function [27].…”
Section: Discussionmentioning
confidence: 98%
“…We chose patients with grades III-V VUR as these children have been shown to have a higher incidence of new scarring. These children have a higher risk group of recurrent UTIs, which would have a greater impact on QOL over patients with grades I and II VUR [21], who are more likely to have spontaneous resolution of the VUR than those with higher grades [22].…”
Section: Methodsmentioning
confidence: 98%
“…The authors showed that the lowest risk of renal scarring after first episode of febrile urinary tract infection was in children in the first year of life and the highest one -in children aged 5 -14 years. It was also demonstrated that the male gender is an independent risk factor for renal scarring (Silva et al, 2009;Mohanan et al, 2008). The risk of post-inflammatory nephropathy development increases with the number of acute pyelonephritis episodes.…”
Section: Introductionmentioning
confidence: 98%
“…Some studies have shown that up to 30% of children requiring renal replacement therapy for end-stage kidney disease had reflux nephropathy [5][6][7][8]. Therefore, acquired scarring associated with VUR from UTIs needs to be differentiated from primary congenital kidney damage from abnormal metanephric development [9] or from obstructive nephropathy [10]. Although the VUR is an established condition of risk for renal scarring after UTI, even infants with a normal urinary tract may be at risk of scarring [11].…”
Section: Introductionmentioning
confidence: 98%